Большой баклан на Северо-Западном Кавказе - Динкевич, М.А.; Мнацеканов, Р.А.; Короткий, Т.В.; Найданов, И.С. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
The present paper summarized all known literary and unpublished data obtained from the regional ornithologists, workers of hunting organizations of the Krasnodar Region and also author's original materials on distribution, numbers and some aspects of biology of the Cormorant in the North-Western Caucasus (the areas of Krasnodar Region and Adygeya Republic). The author's original data have been collected over the period from 1989 to the present time.